Equitable Development Strategy for Lombok Island and Sumbawa Island in West Nusa Tenggara: Analisis Keadilan Pembangunan Berkelanjutan Berdasarkan Tujuan Pembangunan Berkelanjutan di Nusa Tenggara Barat - Ramadhan, Muhammad Satrio (Yayasan Siti Widhatul Faeha, 2025)
Regional inequality between Lombok and Sumbawa Islands in West Nusa Tenggara remains a persistent development challenge that requires collaborative strategies. This study aims to analyze equitable development strategies by integrating Implementation Theory with the Pentahelix Collaboration model. A qualitative case study design was employed, involving 25 purposively selected stakeholders from government, private sector, academia, community, and media. Data were collected through in-depth interviews, field observations, and document reviews, and analyzed thematically using NVivo 12 Plus, supported by Four Quadrant Analysis and Implementation Theory. The findings show that development disparities are rooted in unequal infrastructure distribution, dominance of tourism and services in Lombok, and dependence on mining in Sumbawa despite its vast agricultural and forestry resources. The analysis highlights four key dimensions: coherence through a shared equitable vision, cognitive participation via inclusive stakeholder collaboration, collective action in leveraging natural resources with cultural embeddedness, and reflective monitoring through participatory evaluation. The study concludes that equitable development in West Nusa Tenggara requires not only economic growth but also fair distribution of benefits, strengthened connectivity, and inclusive governance. Scientifically, this research reinforces the applicability of Implementation Theory in regional development studies and recommends adaptive, evidence-based policies that integrate local cultural values and multi-stakeholder collaboration for sustainable and just outcomes.